Ecological awareness of tourists in the coastal areas of Poland - preliminary results of the survey - Głąbiński Zbigniew (Bulletin of Geography. Socio-Economic Series)
The article presents the results of the questionnaire survey studying the level of Polish tourists’ ecological awareness, as well as the degree of their familiarity and interest in the European Ecological Network Natura 2000 in the coastal areas. The survey was held in the years 2012-2013 and was conducted among the respondents visiting the Polish Baltic coast. The majority of tourists (80%) arriving at the seaside for recreational purposes declare a high level of interest in environmental protection and daily pro-ecological behaviours. The most popular sources of information on the environment comprise television and the Internet. The majority of tourists express their interest in recreation in protected areas, yet up to 82% of them are not familiar with the notion of Natura 2000. The knowledge about the locations of Natura 2000 sites in the vicinity of tourists’ holiday spots is equally poor. The visitors to the coastal areas are highly critical of the availability of information on Natura 2000 and indicate the information boards, websites and leaflets as the most desired sources of information.